Antibacterial secondary metabolites from an endophytic fungus, Arthrinium sp. MFLUCC16-1053 isolated from Zingiber cassumunar. Issue 4 (2nd October 2018) - Pansanit, Acharavadee; Pripdeevech, Patcharee
ABSTRACT: Forty-four endophytes were isolated from Zingiber cassumunar and identified morphologically. The ethyl acetate extracts of all endophytes were obtained. The ethyl acetate extracts were subjected to study antibacterial and antioxidant activities. The ethyl acetate extract of the Arthrinium sp. MFLUCC16-1053 showed activity against both gram-positive and gram-negative bacteria. Specifically, the minimum inhibition concentration against Staphylococcus aureus and Escherichia coli was 31.25 and 7.81 µg/mL, respectively. In addition, the crude extract showed highest antioxidant activity in 2, 2-diphenyl-1-picrylhydrazyl scavenging at IC50 value of 28.47 µg/mL. Gas chromatography-mass spectrometry analysis revealed that the extract of the Arthrinium sp. MFLUCC16-1053 contains various antibacterial and antioxidant compounds which are β-cyclocitral, 3 E -cembrene A, laurenan-2-one, sclareol, 2 Z, 6 E -farnesol, cembrene, β-isocomene and γ-curcumene. The fungus Arthrinium sp. MFLUCC16-1053 was also identified by molecular and phylogenetic methods.